Factor Analysis and Level of Effectiveness of Implementation of the Sustainable Food Garden Program (P2l) In Musi Banyuasin Regency - Sakti, Bambang; Purba, Yudhi Zuriah Wirya; Saleh, Wardi (Pascasarjana, Mataram University, 2024)
Nutritional adequacy also needs to be considered by both the community itself and the government in order to avoid stunting. Faced with unfavourable risks, the government has provided a solution in the form of a sustainable food garden program intended for women with middle to lower income. This study aims to determine the level of effectiveness of the programme implementation, the factors that influence the level of effectiveness of the programme, the level of welfare of the Women Farmers Group, and the average amount of reduction in household consumption costs per month. The research was conducted in Musi Banyuasin Regency using a questionnaire. The results showed: 1) the level of effectiveness of the sustainable food home area programme measured from four indicators, namely target accuracy, programme coverage, programme assistance, and achievement of programme objectives is very effective; 2) factors affecting the level of effectiveness are age, education, number of extension services attended, farming experience, number of family members, and land area, while employment status has no effect; 3) there are differences in welfare levels before and after receiving funding assistance for the implementation of the Sustainable Food Home Area programme; 4) the expenditure of farmer women groups after the sustainable food home area programme has decreased on average per member per month, including: KWT Mekar Bersemi 41.8%, KWT Chilli Merah 35.8%, and KWT Kencana Makmur 30.5%.